AVALIAÇÃO DO PADRÃO ESQUELÉTICO VERTICAL DA FACE NA OCLUSÃO NORMAL NATURAL E NAS MALOCLUSÕES DE ANGLE, E SUA CORRELAÇÃO COM A SÍNFISE MANDIBULAR - Carvalho, Mariana Helena Silva (2011)
The purpose of this study was to evaluate cephalometrically, the vertical facial skeletal pattern in subjects with natural normal occlusion and different malocclusions, correlation with the mandibular symphysis and evaluate sexual dimorphism. The sample consisted of 200 cephalometric radiographs divided in five groups based on occlusion type: group A, patients with natural normal occlusion and groups B, C, D and E, patients with malocclusions, each group being divided equally by sex and mean age between 13 and 16 years old. The sample was classified into three morphological patterns of vertical face, according to the facial height ration (FHR), proposed by SIRIWAT & JARABAK or Quotient Jarabak in: Hyperdivergent, Neutral and Hypodivergent. It was used the GoMe.VT variable, from VIGORITO analysis to assess the symphysis inclination and its correlation with the vertical facial patterns. After data collection and statistical tests evaluation; q-square test, "T" Student test and Pearson correlation, it was concluded that Hypodivergent was the most frequent in all patients studied, with 70%, and the greater frequency of this pattern was found in Class II malocclusion, division 2, with 87,5%, prevalence of some other existing standards in different classes of occlusions. We found a positive correlation between the inclination of the mandibular symphysis and Quotient Jarabak only for malocclusion Class I and Class III malocclusion. There was no significant statistical difference between the sexes and the morphology classification when the five groups were compared, however, when the groups were analyzed separately, significant differences were found between the sexes.